PENERAPAN MODEL LIBRARY BASED LEARNING UNTUK MENINGKATKAN LITERASI MEMBACA SISWA PADA MATA PELAJARAN BAHASA INDONESIA KELAS 3 - Khoiril Hidayah; Hesti Majiidatun Naajihah; Eva Luthfi Fakhru Ahsani (Universitas Maritim AMNI Semarang, 2022)
This research was structured with the aim of improving students' reading skills using the library-based learning model for students in class III B MI Nu Nurus Shofa, Bae, Kudus Academic Year 2022/2023. Learning activeness referred to in this study, namely physical activity and mental activity. This type of research is Classroom Action Research (CAR), in which the teacher is the executor of learning while the researcher is the observer. The design of this study uses the Kurt Lewin model. This research was carried out in an odd semester of the 2022/2023 academic year, namely in November 2022. The subjects of this study were students of class III B MI Nu Nurus Shofa Karangnegara Bae Kudus with a total of 37 students where there were 23 male students and 14 students. female student. The object of research is students' reading ability. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in tabular form. The results showed that there was an increase in students' reading ability, namely in the first cycle of 64.8% (good category), then in the second cycle it increased to 89.1% (very good category). This means an increase of 24.3%. Thus the use of the library-based learning model in Indonesian subjects can improve the reading ability of class III B MI Nu Nurus Shofa Karangnegara Bae Kudus.